Comparison of Immunoassays for Measuring Serum Levels of Golimumab and Antibodies Against Golimumab in Ulcerative Colitis: A Retrospective Observational Study. Issue 4 (August 2019) - Berger, Anne-Emmanuelle; Duru, Gerard; de Vries, Annick; Marini, Joseph C.; Aoucheta, Djamila; Cornillie, Freddy; Nancey, Stephane; Detrez, Iris; Gils, Ann; Roblin, Xavier; Paul, Stephane
Abstract : Background: Golimumab is a monoclonal anti–tumor necrosis factor alpha antibody, which is used in ulcerative colitis with an exposure–response relationship. The goal of this study was to compare results obtained with different immunoassays (golimumab and antigolimumab antibodies trough levels). Methods: This study was based on samples from 78 ulcerative colitis patients on golimumab treatment. Golimumab was quantified by either an anti-IgG detection antibody (Theradiag, Marne la Vallée, France) or an antibody directed against golimumab (Sanquin, Amsterdam, The Netherlands, KU Leuven, Leuven, Belgium, and Janssen R&D, San Diego, CA). Bridging drug-sensitive enzyme-linked immunosorbent assays (Theradiag, Janssen R&D, and KU Leuven), a bridging drug-tolerant enzyme-linked immunosorbent assay (Janssen R&D), and a radioimmunoassay (Sanquin) were used to quantify antidrug antibody. Results: Median serum golimumab levels were 4.5, 3.5, 4.9, and 2.4 mcg/mL with Theradiag, Sanquin, KU Leuven, and Janssen R&D assay, respectively ( P < 0.05). Correlation coefficients between assays ranged from 0.9 to 0.97. When using the KU Leuven and Janssen R&D assays, 86% of samples were in the same quartile of distribution of values, and for Sanquin and Janssen R&D assays, this overlap was 80%. The concordance observed for the other pairs was 83% (Sanquin/KU Leuven R&D), 71% (Theradiag/KU Leuven), and 68% (Theradiag/Janssen R&D and Theradiag/Sanquin). The specificity of assays for golimumab was demonstrated. Antidrug antibodies were detected in 28.2% of the samples with the Janssen R&D drug-tolerant assay and in the same 2 patients by the 3 other assays. Conclusions: Performances of these immunoassays were similar in terms of quality, but differences in the quantitative results point to the importance of using the same assay consistently to monitor a patient's treatment. Abstract : Supplemental Digital Content is Available in the Text.